2017
DOI: 10.1212/wnl.0000000000004035
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical thalamic “hubness” predicts surgical outcome in temporal lobe epilepsy

Abstract: A thalamic network associated with seizure recurrence may already be established presurgically. Thalamic hubness can serve as a potential biomarker of surgical outcome, outperforming the clinical characteristics commonly used in epilepsy surgery centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
159
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(169 citation statements)
references
References 39 publications
8
159
2
Order By: Relevance
“…A recent study combined structural connectome features with deep learning, providing high positive and negative predictive values for postoperative outcome prognosis . Data from rs‐fMRI analysis has furthermore shown an association between increased thalamic hubness and seizure recurrence, and these features allowed for individualized prediction with moderate accuracy . Preselection of relevant features may improve accuracies, and a previous rs‐fMRI study has achieved up to 100% accuracy in outcome prediction based on connectivity patterns in temporolimbic and DMN areas .…”
Section: Clinical Connectomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study combined structural connectome features with deep learning, providing high positive and negative predictive values for postoperative outcome prognosis . Data from rs‐fMRI analysis has furthermore shown an association between increased thalamic hubness and seizure recurrence, and these features allowed for individualized prediction with moderate accuracy . Preselection of relevant features may improve accuracies, and a previous rs‐fMRI study has achieved up to 100% accuracy in outcome prediction based on connectivity patterns in temporolimbic and DMN areas .…”
Section: Clinical Connectomicsmentioning
confidence: 99%
“…94 Bottom right, Functional network anomalies in a cohort of ETE showing an increase in local efficiency and higher clustering coefficient compared to healthy controls, suggesting increased local network segregation 95 for individualized prediction with moderate accuracy. 76 Preselection of relevant features may improve accuracies, and a previous rs-fMRI study has achieved up to 100% accuracy in outcome prediction based on connectivity patterns in temporolimbic and DMN areas. 77 As for the lesion-detection paradigms, however, surgical outcome prediction experiments have so far been generally based on small, single-site datasets, motivating additional efforts to share and pool resources.…”
Section: Clinical Connectomicsmentioning
confidence: 99%
“…A functional MRI study performed in patients with unilateral TLE suggested that the thalamus is a "nodal hub" in the organization of epileptogenic networks, in particular in those patients that were not seizure free after en bloc anterior temporal lobectomy. 32 Interestingly, blood-flow increases were seen during seizures in medial thalamic regions and temporal regions by ictal SPECT studies in TLE patients, suggesting a rapid involvement of midline thalamus in the ictal activity. 33 Moreover, thalamic recruitment during focal SLEs originating from the mesial temporal lobe has been described in patients submitted to intracerebral EEG during pre-surgical monitoring, in which electrodes were positioned in the thalamus.…”
Section: Discussionmentioning
confidence: 89%
“…We confirmed here that thalamic midline nuclei are part of the network circuitry of focal limbic seizures. A functional MRI study performed in patients with unilateral TLE suggested that the thalamus is a “nodal hub” in the organization of epileptogenic networks, in particular in those patients that were not seizure free after en bloc anterior temporal lobectomy . Interestingly, blood‐flow increases were seen during seizures in medial thalamic regions and temporal regions by ictal SPECT studies in TLE patients, suggesting a rapid involvement of midline thalamus in the ictal activity .…”
Section: Discussionmentioning
confidence: 99%
“…Following methodological advances, several studies have addressed this limitation by applying graph theoretical and machine learning approaches to infer neurosurgical outcome at the individual patient level (for a review see Senders et al, 2018). In particular, several studies have tried to find biomarkers that predict seizure freedom after epilepsy surgery (for example Bonilha et al, 2013Bonilha et al, , 2015He et al, 2017;Ji et al, 2015;Morgan et al, 2017;Munsell et al, 2015;Taylor et al, 2018;van Dellen et al, 2014). Others have evaluated machine learning strategies designed to predict survival in glioma (Emblem et al, 2009(Emblem et al, , 2015 and traumatic brain injury patients (Rughani et al, 2010).…”
Section: Introductionmentioning
confidence: 99%